SELECTION OF THE BEST VARIETIES OF CHERRY FRUITS BY THE METHOD OF MULTI-CRITERIA OPTIMIZATION - Василишина, О. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2019)
The production of quality products and their efficiency is a pressing issue today. The solution of which is inextricably linked to the introduction of new varieties with a high content of antioxidants, pectins, which have healing and preventive properties. To conduct research in 2016 - 2018 at the L.P. Symyrenko experimental station IS NAAN the following varieties of cherry fruits were selected: Alpha, Zhadan, Chance, Elegant, Artemenko Memory, Optimist, Podbelskaya. The cherry was harvested in the consumer stage of ripeness during the first decade of July. According to the complex of physicochemical and organoleptic parameters, the selection of the best variety of cherry fruits was performed by the method of multicriteria optimization. The aim of the work was, on the basis of a comparative analysis of a set of physicochemical and organoleptic indicators of cherry fruits, using multicriteria optimization, to determine the best varieties recommended for production. The results of studies showed that the weight of cherry fruits ranged from 4,2 to 5,2 g. The content of soluble solids in cherry fruits was at the level of 15,26–15,89% and was predominant for cherries in Artemenko memory and the lowest in Podbelska variety. The sugar content of cherry fruits was 10,14 −10,96%. The level of titratable acids that determine the taste of cherry fruits together with the gourds is in the range from 1,67 to 2,02%. It is the highest for cherry fruits of the Artemenko memory, and the lowest for the Elegant variety. The cherry fruits of the experimental varieties have a significant content of ascorbic acid − 19,15−16,25 mg/100 g. The cherries of the Artemenko memory, and the lowest of the Optimist variety, prevail in the fruits. The tasting rating of cherry fruits is 8−8,7 points. According to the complex of the mentioned above physicochemical and organoleptic indicators by the method of multicriteria optimization such varieties of cherry fruits as Artemenko Memory, Alpha and Zhadana are recommended for production implementation